THE IMPACT OF RELATIONAL DEMOGRAPHY AND SUBUNIT DIVERSITY ON PERCEIVED CHANGE EFFECTIVENESS: AN EMPIRICAL STUDY IN KNOWLEDGE-BASED ORGANIZATIONS - Mascia, D.; Dello Russo, S.; Morandi, F. (“Research Advances in Organizational Behavior and Human Resources Management” workshop, 2016)
In this paper we analyze the effectiveness of an organizational change in terms of individual job satisfaction and physicians’ perceived group collaboration after the change, and explore how relational demography and diversity in newly created subunits affect these two outcomes. We consider two attributes of individual diversity that loom large in knowledge-based organizations, namely organizational tenure and educational background. Moreover, in keeping with the diversity literature, we look at multiple levels of diversity. In the framework of relational demography, we develop hypotheses at the individual level of analysis about the impact of subordinate-supervisor differences on employee job satisfaction and perceived collaboration after the change. In the framework of organizational diversity, we advance the hypothesis that the implementation lag, i.e. the time elapsed from the implementation of restructuring intervention, moderates the positive relationships between subunit diversity and individual perception of change effectiveness. Data used in the analysis pertain to 745 physicians nested in 40 hospital departments, and were collected through mixed methods (surveys and biographic data accessing). We employ multilevel analysis to test our theoretical predictions. Our study findings document that individual job satisfaction after the change is positively affected by tenure difference between subordinates and supervisors, and that the positive effect that subunit diversity has on individual job satisfaction and perceived group collaboration is stronger when the implementation lag is longer. We discuss the theoretical contribution and practice implications of our findings.